Association Between Serum 25-Hydroxyvitamin D Levels and Autoimmune Thyroid Disorders in Iraqi Adults with Type 2 Diabetes Mellitus - Umer Jameel Ibrahim; Abdulmunem Kurdi Abdullah; Khalaf Naeef Mohamed (American Journal of Biology and Natural Sciences, 2026)
Vitamin D is very important for immune regulation and has been implicated in the pathogenesis of autoimmune diseases, such as autoimmune thyroid disorders. It has been established that patients with type 2 diabetes mellitus (T2DM) have chronic low-grade inflammation and immune dysregulations that might predispose them to autoimmune thyroid disease. The purpose of this study was to explore the correlation between serum 25 hydroxyvitamin D levels and autoimmune thyroid disease in adults with T2DM. We have found that a low level of vitamin D may be associated with increased autoimmune responses against the thyroid gland, and this may be one of the factors that lead to the onset and advancement of autoimmune thyroid diseases in this group of people. The paper highlights the need to assess vitamin D status in patients with T2DM as a potential preventive or therapeutic measure to reduce the risk of thyroid autoimmunity and its complications. More longitudinal research and clinical interventions are justified to clarify the causal association and to investigate the utility of vitamin D supplementation in the high-risk population.